Acta Crystallographica Section B: Structural Science, Crystal Engineering and Materials - Acta Crystallographica Section B: Structural Science, Crystal Engineering and Materials (Wiley, 2026)
Acta Crystallographica Section B: Structural Science, Crystal Engineering and Materials journal publishes scientific articles related to the structural science of compounds and materials in the broadest sense. Knowledge of the arrangements of atoms is often the key to understanding physical and chemical phenomena and is crucial for the design of new materials and supramolecular devices. We are the forum for contributions in these areas. We feature experimental studies, including those that relate to crystal growth, as well as those based on theoretical approaches, such as crystal structure prediction, structure-property relations and the use of crystal structure databases.
FI 0.56
Q3
Keywords: Earth; Space & Environmental Sciences; Crystallography; Cristalografía; Acuerdos transformativos; Transformative agreements; Predicción de la estructura cristalina; Relaciones estructura-propiedad; Bases de datos de estructuras cristalinas